Bleeding gastric teratoma on adult patient (2020)
A 31-year-old patient presented with abdominal pain, hematemesis, and melena. Digestive endoscopy demonstrated a tumor in the lesser curvature. Computed tomography scan demonstrated an expansive, solid, and cystic mass, with central and intramural calcifications, located in the epigastrium, in close contact with the wall of the lesser curvature (Figure A). The patient developed acute anemia and underwent emergency surgery. The pathology report showed a giant gastric tumor measuring (12× 8× 5 cm). On serial sectioning, cystic and solid areas with mucinous material, adipose tissue, and scattered hairs (arrows) were identified (Figure B). Histopathology revealed several well-differentiated tissues derived from the germ layers, adipose tissue and skin with its appendages (Figure C). The Ki-67 was reactive in the basal layer of the squamous epithelium (Figure D). No malignancy was found in the tumor.